Low Dose Rate X-Ray Radiation Fields Implementation for Study of Energy Response of the Dosimeters Based on Scintillation Detectors - A. V. Novichenko; R. V. Lukashevich; K. G. Senkovsky (Приборы и методы измерений)
Near background low dose rate measurements are important part of the environmental radiation monitoring. It is possible to fulfill energy response verification for the high sensitive dosimeters based on inorganic scintillation detectors in low energy region when creating reference X-ray fields with dose rates up to 5 µSv/h. The aim of this work was to create and study reference X-ray fields with low dose rate and narrow spectrum in the energy range from 15 to 250 keV using high-purity metal filters as a part of X-ray irradiator of AT300 X-ray calibration facility.To determine the main characteristics of created X-ray fields highly sensitive comparators of photon radiation based on NaI(Tl) scintillation detectors was used. The comparators were developed in “ATOMTEX”. To verify comparators energy response the reference AT5350/1 dosimeter and ionization chamber TM32003 with sensitive volume 10000 cm3 were used.Characteristics of X-ray fields that were created on the AT300 X-ray calibration facility to verify the energy response of high sensitive dosimeters based on scintillation detectors were investigated. The possibility to calibrate high sensitive dosimetric measuring instruments based on scintillation detectors in the energy range up to 250 keV in X-ray beams was shown.